Validation of novel reference genes for RT‐qPCR studies of gene expression in Xenopus tropicalis during embryonic and post‐embryonic development. Issue 6 (29th April 2013) - Dhorne‐Pollet, Sophie; Thélie, Aurore; Pollet, Nicolas
<x xml:space="preserve">Abstract</x> Background: Accurate interpretation of transcriptome profiling by quantitative PCR requires the establishment of species‐specific standards. However, the selection of reference genes for assessing RNA expression profiles in Xenopus laevis and Xenopus tropicalis was mostly based on historical reasons and they often only reflect the traditions of a laboratory. Results: We investigated the expression stability of 10 genes (dicer1, drosha, eef1a1, elavl3, gsc, h4, odc1, rpl8, smn2, tbp), 8 of which are commonly used as internal controls in published RT‐qPCR experiments. We defined specific primer pairs and evaluated their suitability as reference genes by performing RT‐qPCR expression profiling in Xenopus tropicalis. Gene expression stability was assayed in a set of 15 developmental stages from the egg to the froglet, and in dissected embryos. Conclusions: Overall, we determined a set of qualified reference genes for distinct developmental periods. We recommend the use of dicer1, drosha, eef1a1, and smn2 from early embryonic development up to the end of metamorphosis. During early embryogenesis drosha, eef1a1, smn2 are suitable. For the whole post‐embryonic development and for metamorphic stages including pro‐metamorphosis and metamorphic climax, we recommend the use of drosha and smn2. These reference genes should prove their usefulness for data comparison across studies. Developmental Dynamics 242:709–717, 2013. © 2013 Wiley Periodicals, Inc.